A GENERALIZED NET MODEL FOR ACCESSING INFORMATION RESOURCES IN A SECURE ENVIRONMENT (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The purpose of the study is to describe and present the process of accessing information resources in a secure military computer network as generalized net model. A simulation of the model was carried out using specialized software for working with generalized nets - GN IDE, and the most important results are visualized in the report.